The Effect of Job Training, Work Discipline and Work Motivation on Employee Performance at the Lamongan Regency Drinking Water Perumda Office - Elmia Sadiyah; Abid Muhtarom; Mohammad Yaskun (Jurnal Multidisiplin Sahombu, 2025)
Human resources are very important assets that cannot even be separated from an organization, both institutions and companies. Given the importance of the role of human resources in a corporate organization in today's era. The purpose of this study is to find out how the influence of job training, work discipline and work motivation on employee performance, so the following hypotheses are proposed: It is suspected that the variables of job training, work discipline and work motivation have an influence on employee performance partially and simultaneously, and it is suspected that the variables of work discipline are the dominant variables that affect employee performance. This research is a quantitative research, the type of data used is primary data and secondary data, data collection techniques using questionnaires, interviews, documentation. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression test, multiple correlation, determination coefficient, t test, F test, which aims to test hypotheses that have been determined and tested with spss analysis tools. In this study, there were a total of 61 samples from 158 populations taken from the data of PERUMDA Lamongan Regency Drinking Water employees. The results of the analysis showed that all the data collected were valid and reliable, there were no multikos and heteros. The SPSS output results also show that the multiple correlation value is 0.932 and the determination coefficient (R2) is 0.869. From the calculation of the t-table, the result was 0.67867 and t-calculation X1=2.771, X2=6.228, X3=8.803, thus showing that there was a partial or individual influence. Meanwhile, after calculating f-calculus, the f-calculation value was 126,486 and the f-table was 2.51 which shows that there is an influence simultaneously or together. Meanwhile, from the results of the multiple linear regression analysis test, the value of Y = 1.171 + 0.250X1 + 0.510X2 + 0.420X3 was obtained. From the results of this study, it can be concluded that job training, work discipline and work motivation can be seen from the t-calculation > t-table. Job training, work discipline and work motivation simultaneously affect employee performance as seen from the results of f-calculation > f-table, and work discipline has a more dominant influence on employee performance.